2021
DOI: 10.1016/s0140-6736(21)01921-8
|View full text |Cite
|
Sign up to set email alerts
|

Age-stratified and blood-pressure-stratified effects of blood-pressure-lowering pharmacotherapy for the prevention of cardiovascular disease and death: an individual participant-level data meta-analysis

Abstract: Background The effects of pharmacological blood-pressure-lowering on cardiovascular outcomes in individuals aged 70 years and older, particularly when blood pressure is not substantially increased, is uncertain. We compared the effects of blood-pressure-lowering treatment on the risk of major cardiovascular events in groups of patients stratified by age and blood pressure at baseline. MethodsWe did a meta-analysis using individual participant-level data from randomised controlled trials of pharmacological bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
83
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(97 citation statements)
references
References 42 publications
7
83
1
6
Order By: Relevance
“… 44 In addition, these benefits of BP lowering were seen in individuals aged up to 85 years. 45 In the STEP study, a 5‐mmHg reduction in office SBP was associated with an 18% reduction in total cardiovascular disease risk, a 23% reduction in the risk of stroke and coronary artery disease, and a 58% reduction in heart failure risk. These findings showing greater reductions in cardiovascular risk in the STEP study than in SPRINT and the BPLTTC (Table 2 ), suggest that strict BP control is probably more effective for cardiovascular disease prevention in Asians than in Westerners.…”
Section: The Hope Asia Network: Seven Action Approaches For Hypertens...mentioning
confidence: 99%
“… 44 In addition, these benefits of BP lowering were seen in individuals aged up to 85 years. 45 In the STEP study, a 5‐mmHg reduction in office SBP was associated with an 18% reduction in total cardiovascular disease risk, a 23% reduction in the risk of stroke and coronary artery disease, and a 58% reduction in heart failure risk. These findings showing greater reductions in cardiovascular risk in the STEP study than in SPRINT and the BPLTTC (Table 2 ), suggest that strict BP control is probably more effective for cardiovascular disease prevention in Asians than in Westerners.…”
Section: The Hope Asia Network: Seven Action Approaches For Hypertens...mentioning
confidence: 99%
“…Impressive cardiovascular benefits have been observed with intensive BP control (SBP target, <120 mmHg), as compared with standard BP control (SBP target, <140 mmHg), in the SPRINT (Systolic Blood Pressure Intervention Trial), even in patients 75 years of age or older [ 7 , 8 ]. A most recent meta-analysis including 51 randomized trials with over 350,000 participants from the BPLTTC (The Blood Pressure Lowering Treatment Trialists’ Collaboration) showed that BP lowering is effective in older people for reducing major cardiovascular events, down to below 120/70 mmHg [ 9 ]. The STEP (Strategy of Blood Pressure Intervention in the Elderly Hypertensive Patients) study—a multicenter, randomized, controlled trial conducted in China, provided new direct evidence that intensive BP treatment (SBP target, 110 mmHg to <130 mmHg) benefits older hypertensive patients (aged 60-80 years) and reduces the incidence of cardiovascular events than standard treatment (target 130 mmHg to <150 mmHg) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over time, there was a steady shift of the age band of interest to more elderly patients and to lower blood pressure targets. A recently published meta-analysis [ 3 ] included 358,707 patients from 51 trials, aged 21–105 years (median, 65 years; interquartile range, 59–75 years). It showed no evidence for any clinically meaningful heterogeneity of relative risk reduction by blood-pressure lowering therapies across different baseline blood-pressure categories in any age group.…”
mentioning
confidence: 99%
“…It showed no evidence for any clinically meaningful heterogeneity of relative risk reduction by blood-pressure lowering therapies across different baseline blood-pressure categories in any age group. Per 5-mm Hg systolic blood pressure reduction, the hazard ratios of major cardiovascular events were 0.82 (95% confidence interval, 0.76–0.88), 0.91 (0.88–0.95), 0.91 (0.88–0.95), 0.91 (0.87–0.96), and 0.99 (0.87–1.12) in the age bands <55 years, 55–64 years, 65–74 years, 75–84 years and ≥85 years with similar patterns of relative risk reduction per 3-mm Hg lower diastolic blood pressure [ 3 ]. However, the reductions in absolute risk produced by blood-pressure lowering increased with advancing age.…”
mentioning
confidence: 99%
See 1 more Smart Citation